2012
DOI: 10.1590/s1983-14472012000400025
|View full text |Cite
|
Sign up to set email alerts
|

Método bundle na redução de infecção de corrente sanguínea relacionada a cateteres centrais: revisão integrativa

Abstract: Trata-se de uma revisão integrativa da literatura, que objetivou identificar intervenções baseadas em evidência que compõem o método bundle, designados à redução de infecção de corrente sanguínea relacionada ou associada a cateter intravenoso central. Para a coleta de dados online, em bases nacionais e internacionais, foram utilizados a palavra-chave bundle e os descritores catheter-related infection, infection control e central venous catheterization, resultando, após aplicação dos critérios de inclusão, amos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
7

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
9
0
7
Order By: Relevance
“…16 The knowledge of the bundle of measures for the control of infection by the use of bladder catheter is of great relevance, being necessary that high adherence by the team of professionals to the recommended measures occurs, so that the proposed guidelines are applied jointly, promoting the safety culture of the patients. 17 However, 46.3% of the professionals participating in this study, when asked if they had knowledge about the existence of the urinary tract infection bundle, reported that they did not know about it and 14.6% did not respond to the question. It has been observed that the term bundle is not routinely used, but rather the term "package of measures".…”
mentioning
confidence: 88%
“…16 The knowledge of the bundle of measures for the control of infection by the use of bladder catheter is of great relevance, being necessary that high adherence by the team of professionals to the recommended measures occurs, so that the proposed guidelines are applied jointly, promoting the safety culture of the patients. 17 However, 46.3% of the professionals participating in this study, when asked if they had knowledge about the existence of the urinary tract infection bundle, reported that they did not know about it and 14.6% did not respond to the question. It has been observed that the term bundle is not routinely used, but rather the term "package of measures".…”
mentioning
confidence: 88%
“…A veia subclávia se sobressai quanto ao local de punção de nutrição parenteral, transfusão sanguínea, infecção subjacente no momento da inserção do cateter, mais de uma indicação para uso do dispositivo e sítio de inserção femoral (14)(15)(16) .…”
Section: Artigounclassified
“…The elements of emphasis that make up the bundles are: hand hygiene, use of chlorhexidine alcohol as an antiseptic for skin preparation, use of maximum barrier precaution, nonuse of femoral vein accesses, and daily verification of the need for catheter permanence (11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%